2018
DOI: 10.1039/c8ra07671e
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity and vibrational studies induced phase transitions in [(C2H5)4N]FeCl4

Abstract: Complex impedance spectra of [(C2H5)4N]FeCl4 at different temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…22 For the quaternary amine cations [(C n H 2n+1 ) 4 N] + bound to an iron(III) chloride, the increase in the number of carbon atoms in the alkyl chain makes it possible to decline the structural stability of the anion (FeCl 4 ). 23 The transition temperatures are dependent on the thermal history of the samples 24 and contrary results are reported in literature 23,[25][26][27] for the [(C 2 H 5 ) 4 N]FeCl 4 (n ¼ 2) compound. Indeed, the Differential Thermal Analysis (DTA) measurements performed by D. Wyrzykowski et al…”
Section: Introductionmentioning
confidence: 68%
“…22 For the quaternary amine cations [(C n H 2n+1 ) 4 N] + bound to an iron(III) chloride, the increase in the number of carbon atoms in the alkyl chain makes it possible to decline the structural stability of the anion (FeCl 4 ). 23 The transition temperatures are dependent on the thermal history of the samples 24 and contrary results are reported in literature 23,[25][26][27] for the [(C 2 H 5 ) 4 N]FeCl 4 (n ¼ 2) compound. Indeed, the Differential Thermal Analysis (DTA) measurements performed by D. Wyrzykowski et al…”
Section: Introductionmentioning
confidence: 68%
“…It is found that the spectrum exhibits two different regions: (1) a low frequency plateau region (conductivity is almost independent of frequency and equal to dc conductivity) and (2) a high frequency conductivity dispersion region (increasing frequency conductivity increases due to mobility of charge carriers). This behavior follows Jonscher's power law, which is related to the dynamics of ionic hopping transport between localized sites and given by the following expression: σ=σdc+σac=σdc+Aωs where σ dc is the frequency independent conductivity, s the frequency exponent, displaying information about the degree of interaction pertaining to the charge carriers with its environment and generally having a value in the range of 0 ≤ s ≤ 1 . However, some studies showed that 1 is not a limited value for S. In fact, for s < 1, it indicates that the hopping of the charge carriers is in a translational motion and, for s > 1, the motion is a localized one .…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the spectrum exhibits two different regions: (1) a low frequency plateau region (conductivity is almost independent of frequency and equal to dc conductivity) and (2) a high frequency conductivity dispersion region (increasing frequency conductivity increases due to mobility of charge carriers). This behavior follows Jonscher's power law, [32,33] which is related to the dynamics of ionic hopping transport between localized sites and given by the following expression:…”
Section: Conductivity Study Conduction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…For large values of W M /K B T, Equation becomes: S=16KBTWM Figure shows the variation of (1‐S) as a function of temperature. The linear fit of the curve in region I, and II was used to determine the value of W M , which equals 0.24 and 0.43 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%